(3CReGJ GdPgH aj GdYdGbGJ GdfbOjI GdOhdjI (B/s - (3YWhf, eQhGfs ((3Yjf edjdI(B: s (3OGQ GdgOi(B, s)
(3XghQ hJWhQ GdfbhO ,GdCfXeI GdfbOjI GdeYOfjI ,JWhQ OhQ GdPgH aj GdCfXeI GdfbOjI GdMOjKI,GdfXGe GdfbOj GdhQbj,NUGFU JWhQ GdCfXeI GdfbOjI,GdPgH hGdOhdGQ aj GdfXGe GdfbOj GdOhdj,Mbhb GdSMH GdNGUI,fTGW UfOhb GdfbO GdOhdj hfXGe Mbhb GdSMH, GdYQV hGdWdH ,GdCgejI GdfSHjI ddPgH,eTcdI GdPgH aj GdYdGbGJ GdfbOjI(B.s
(3GdeQGLY U(B.245s
Keywords: (3GdCReGJs; (3GdYdGbGJ GdGbJUGOjI GdOhdjIs; (3GdfXGe GdfbOj GdOhdjs; (3GdfbhOs